Novel strategies to diagnose prosthetic or native bone and joint infections. Issue 3 (4th March 2022) - Van Belkum, Alex; Gros, Marie-Francoise; Ferry, Tristan; Lustig, Sebastien; Laurent, Frédéric; Durand, Geraldine; Jay, Corinne; Rochas, Olivier; Ginocchio, Christine C.
ABSTRACT: Introduction: Bone and Joint Infections (BJI) are medically important, costly and occur in native and prosthetic joints. Arthroplasties will increase significantly in absolute numbers over time as well as the incidence of Prosthetic Joint Infections (PJI). Diagnosis of BJI and PJI is sub-optimal. The available diagnostic tests have variable effectiveness, are often below standard in sensitivity and/or specificity, and carry significant contamination risks during the collection of clinical samples. Improvement of diagnostics is urgently needed. Areas covered: We provide a narrative review on current and future diagnostic microbiology technologies. Pathogen identification, antibiotic resistance detection, and assessment of the epidemiology of infections via bacterial typing are considered useful for improved patient management. We confirm the continuing importance of culture methods and successful introduction of molecular, mass spectrometry-mediated and next-generation genome sequencing technologies. The diagnostic algorithms for BJI must be better defined, especially in the context of diversity of both disease phenotypes and clinical specimens rendered available. Expert opinion: Whether interventions in BJI or PJI are surgical or chemo-therapeutic (antibiotics and bacteriophages included), prior sensitive and specific pathogen detection remains a therapy-substantiating necessity. Innovative tests for earlier and more sensitive and specific detection of bacterial pathogens in BJI are urgently needed.